Contribution of equilibrative nucleoside transporter (ENT) 2 to fluorouracil transport in rat placental trophoblast cells. Issue 2 (April 2017) - Takagi, Akinori; Nishimura, Tomohiro; Akashi, Tomoya; Tomi, Masatoshi; Nakashima, Emi
Abstract: Fluorouracil is used for treatment of breast cancer even in pregnant women, except during fetal organogenesis. The purpose of this study was to clarify the transport mechanism of fluorouracil at the rat placental barrier. Maternal-to-fetal transfer of [ 3 H]fluorouracil in rats at gestational day 19.5 was saturable and much higher than that of [ 14 C]sucrose. The uptake of [ 3 H]fluorouracil was also saturable in rat placental trophoblast TR-TBT 18d-1 cells, which express both equilibrative nucleoside transporter (ENT) 1 and ENT2. Nitrobenzylthioinosine (NBMPR) at 0.1 μM had no effect on [ 3 H]fluorouracil uptake by TR-TBT 18d-1 cells, but 100 μM NBMPR almost completely inhibited the saturable component, suggesting involvement of ENT2, rather than ENT1 in the transport. Rat ENT2 cRNA-injected oocytes showed significantly increased [ 3 H]fluorouracil uptake compared with water-injected oocytes, while rat ENT1 cRNA-injected oocytes did not show an increase of [ 3 H]fluorouracil uptake. The Michaelis–Menten constant for rat ENT2-mediated uptake of [ 3 H]fluorouracil was 4.21 mM. The expression profile of ENT2 mRNA in rat placenta during pregnancy was almost constant from 13.5 to 21.5 days of gestation. In conclusion, ENT2 appears to be the mediator of fluorouracil transport in rat placental trophoblast cells. Graphical abstract: